Disease awareness campaigns in printed and online media in Latvia: cross-sectional study on consistency with WHO ethical criteria for medicinal drug promotion and European standards - Teresa Leonardo Alves (BMC Public Health, 2018)
Abstract Background European legislation prohibits direct-to-consumer advertising of prescription medicines, but allows drug manufacturers to provide information to the public on health and diseases. Our aim was to measure the frequency of disease awareness campaigns in Latvian media and assess their compliance with international and European standards. Methods Materials on health/disease and treatments were collected between April and September 2015 from 12 newspapers and magazines and six online portals. Disease awareness campaigns were assessed using a previously developed instrument based on the WHO Ethical Criteria for Medicinal Drug promotion and European standards (EU law and pharmaceutical industry self-regulatory guidelines). Collected materials were used to examine the information provided on medical conditions and their diagnosis and treatment. The inter-rater reliability was calculated. Results We collected 263 materials from print (n = 149) and online media (n = 114); 94 were news items and 169 were disease-awareness advertisements. Cancer, cardiovascular problems, allergies and respiratory diseases were common topics. Of the 157 campaigns assessed, non-compliance was identified in 149 cases (inter-rater reliability 90%), mainly due to misleading or incomplete information, lack of balance and the absence of a listed author/sponsor. Six disease awareness campaigns directly mentioned a pharmaceutical product by brand name and other four included the logo or name of a manufacturer, referred to a condition and indirectly mentioned a treatment, all in contravention with European law. Conclusions The compliance of disease awareness campaigns in Latvian media with international and European standards is low. This raises concerns about the nature of information being conveyed. Through lack of balance, missing sponsorship information, and misleading or incomplete information, these campaigns could contribute to inaccurate self-diagnosis and generate demand among those who might not need medical treatment.